Exploring the 7p22.1 Chromosome as a Candidate Region for Autism - Bayou, Nadia (Hindawi Publishing Corporation, 2010)
A high incidence of de novo chromosomal aberrations in a population of persons with autism suggests a causal relationship between certain chromosomal aberrations and the occurrence of autism. A previous study on a Tunisian boy carrying a t(7;16) translocation identified the 7p22.1 as a positional candidate region for autism on chromosome 7. The characterization of the chromosomal breakpoints helped us to identify new candidate regions on chromosome 16p11.2 which contain no known genes and the other one on 7p22.1 containing a portion of genes (NP 976327.1, RBAK, Q6NUR6 also called RNF216L and MMD2). We proposed Q6NUR6 (RNF216L) as a candidate gene for autism due to its vicinity to the translocation breakpoint on the chromosome derivative 7. Q6NUR6 is predicted to be an E3ubiquitin-ligase. Quantitative PCR demonstrates that Q6NUR6 gene has an ubiquitous expression and that it is strongly expressed in fetal and adult brain. The Q6NUR6 expression is increased in the patient blood cells in comparison to controls. This is the first report of Q6NUR6 gene (E3 ubiquitin ligase TRIAD3 EC 6.3.2) increasing blood levels in a patient with autism. It's probably caused by a position effect involving this gene and modifying its expression.